A Reusable Unsupported Rhenium Nanocrystalline Catalyst for Acceptorless Dehydrogenation of Alcohols through γ‐C–H Activation1. (26th November 2013) - Yi, Jing; Miller, Jeffrey T.; Zemlyanov, Dmitry Y.; Zhang, Ruihong; Dietrich, Paul J.; Ribeiro, Fabio H.; Suslov, Sergey; Abu‐Omar, Mahdi M.
Abstract Rhenium nanocrystalline particles (Re NPs), of 2 nm size, were prepared from NH4ReO4 under mild conditions in neat alcohol. The unsupported Re NPs convert secondary and benzylic alcohols to ketones and aldehydes, respectively, through catalytic acceptorless dehydrogenation (AD). The oxidant‐ and acceptor‐free neat dehydrogenation of alcohols to obtain dihydrogen gas is a green and atom‐economical process for making carbonyl compounds. Secondary aliphatic alcohols give quantitative conversion and yield. Transmission electron microscopy (TEM), X‐ray photoelectron spectroscopy (XPS), Re K‐edge X‐ray absorption near‐edge structure (XANES), and X‐ray absorption fine structure (EXAFS) data confirmed the characterization of the Re NPs as metallic rhenium with surface oxidation to rhenium(IV) oxide (ReO2). Isotope labeling experiments revealed a novel γ‐CH activation mechanism for AD of alcohols.